Cattle MHC: Evolution in action? - Ellis, S.A.; Ballingall, Keith T. (Wiley, 1999)
Because major histocompatibility complex (MHC) genes play a major role in the development of acquired immune responses, it is essential to obtain comparative information on their organisation, expression and possible functional dichotomies in different species. In human, three classical, polymorphic class I genes (HLA-A, B- and -C) and four expressed A/B class II gene pairs (HLS-DM -DP, -DR) are each present on all haplotypes. With the exception of the HLA-DRB loci, it has been assumed that a similar rigid organisational situation exists in other manmalian species. However, extensive analysis of the bovine MHC (BoLA) at both the genomic and transcriptional levels has revealed a degree of genetic fluidity not described in other species. None of the four (or more) classical class I genes identified is consistently expressed, and haplotypes differ from one another in both the number and composition of expressed class I genes. Similarly, in the class II region, the number of DQ genes varies between haplotypes in both number and composition. These variations in both class I and II (which appear to reflect differences at the genomic level) are likely to play an important role in cattle immune responses. The observed phenotypic differences in cattle demonstrate very clearly the dynamic nature of the MHC region. This review addresses the functional impact of such variation in different breeds and populations, and its significance in terms of MHC evolution.